Pengaruh Pemberian Masase dalam Penurunan Nyeri Kepala pada Lansia Penderita Hipertensi di Desa Dasan Tereng Wilayah Kerja Puskesmas Narmada - Rispawati, Baik Heni; Halid, Sopian; Supriyadi, Supriyadi (Sekolah Tinggi Ilmu Kesehatan YARSI Mataram, 2020)
From the Word Organization (WHO, 2014) shows one in three adults throughout the world suffer from hypertension. The prevalence of hypertension is expected to continue to increase and is predicted in 2025 as many as 29% of adults worldwide suffer from hypertension, while in Indonesia the figure reaches 31.7% (Ministry of Health Republic of Indonesia, 2016). The purpose of this study was to determine the effect of giving head massage to reduce headache in elderly people with hypertension in the Dasan Tereng Village, Narmada Health Center. This type of research is a pre experiment with the One Group Pretes Post test approach. The data collection technique used was accidental sampling with 57 respondents. Data collection uses observation sheets. The results of the study with the average value of the pain scale intensity on hypertensive clients before being given a pain intensity massage of 59.09 and the average after a head massage with a value of 59.09%, Then the calculated value shows a p value of 0.002, which means more smaller than the critical limit of 0.05 which means H1 is accepted and H0 is rejected. There is an influence of head massage on the reduction of headache in patients with hypertension in the Dasan Tereng village, the working area of the Narmada Public Health Center. It is expected to improve health programs and motivate, facilitate and support activities, especially head massage activities so that they can be used as routine programs such as health program socialization